Enhancing Logit Modeling With GIS Integration for Advanced Spatial Analysis: A Case Study of Multimodal Transport Preferences Between Istanbul and Ankara - Adalıoğlu, İsmail; Ergün, Murat (Wiley, 2025)
ABSTRACTThis paper proposes an integrated approach that enhances traditional logit modeling by dynamically incorporating Geographic Information Systems (GIS) for more advanced spatial analysis. Conventional logit models often overlook spatial factors in decision making, but this approach incorporates spatial data to provide a deeper understanding of how geography influences choices. By using GIS in the postmodeling phase, spatial utility functions are calculated to visualize and analyze decision patterns across regions. A case study on multimodal public transportation preferences between Istanbul and Ankara, using survey data from 2757 participants, validates this approach. The results reveal distinct spatial patterns, with private vehicle users favoring airports due to better connectivity and public transport users preferring bus terminals. These findings emphasize the strategic importance of transportation hubs and the influence of spatial accessibility on user preferences. This GIS‐logit integration offers significant implications for transportation planning and policy, providing a scalable framework for analyzing spatially influenced decisions in various fields.